Effect of Sn Addition in Preprecipitation Stage in Al-Cu Alloys: A Correlative Transmission Electron Microscopy and Atom Probe Tomography Study - Homma, T; Moody, M; Saxey, D; Ringer, S (2012)
The effect of a trace addition of Sn (0.01 at. pct) in Al-1.7Cu (at. pct) alloy in the preprecipitation stage has been investigated by atom probe tomography (APT) and transmission electron microscopy (TEM). APT demonstrates that Sn clusters form independently of Cu in the as-quenched (AQ) state in Al-1.7Cu-0.01Sn alloy. The Sn clusters lead to the rapid nucleation of β-Sn precipitates during increased temperature aging. The APT analysis also indicates that Cu tends to cluster with Sn when the increased temperature aging commences. The TEM experiments revealed that GP zones formed during the first 30 seconds of aging at 473 K (200 °C) in both alloys. These GP zones were unstable and underwent a reversion reaction such that they were not detected after 180 seconds of aging. This process is thought to arise from heating rate effects and, at these higher temperatures, supplies a flux of Cu atoms that results in the heterogeneous nucleation of the (Al 2Cu) phase. © The Minerals, Metals and Materials Society and ASM International 2012.